Rancang Bangun Alarm Kebocoran Gas Lpg Dengan Sensor MQ-2 - Syahrin, Elvin; Doni, Rahmad; Nasution, Fitri Pranita; Farhan Sya'bandi Nasution; Muhammad Andy Syahputra (Jurnal Sains dan Teknologi (JSIT), 2022)
In today's human life, both at home and in industry, it is very necessary to have LPG gas to meet daily needs. We know that gas can also have a bad impact, especially if there is no known leak from the LPG gas cylinder or storage area. The cause of this gas cylinder leak could be a leak in the hose, tube or also the regulator that is not installed properly and the gas cylinders that are distributed are of poor quality or physically damaged. This study aims to produce a tool that is an LPG gas cylinder leak alarm using the MQ-2 sensor. The way this tool works is, the Arduino UNO reads the MQ-2 sensor with analog data output, if it reads that there is gas leaking, the alarm will sound.